Genetic diversity analysis for malting grain traits in barley (Hordeum vulgare) - YADAV, R; JAGSHORAN, JAGSHORAN (The Indian Journal of Agricultural Sciences, 2013)
An expetiment was conducted during 1995-96 and 1996-97 to assess the extent of genetic variation in the set of barley (Hordeum vulgare L.) lines comprising both exotic (bred mainly for feed and malt) and indigenous collections (bred mainly for food) through a cluster analysis for 6 malting grain characteristics, viz thin kernel (%), l000-kernel weight, seed shape, germinative energy, water sensitivitiy/tolerance and protein (%). The results indicated the composition of clusters on the line of their source. Cluster 1 comprises both indigenous and exotic collections with desirable type of grain characters. One thousand kernel weight showed the significant negative correlation with the of thin grains (%).